Clinical Profile and Outcome of Pediatric Mitochondrial Myopathy in China - Hu, Chaoping; Li, Xihua; Zhao, Lei; Shi, Yiyun; Zhou, Shuizhen; Wang, Yi (Frontiers in Neurology, 2020)
Introduction Mitochondrial myopathy in children has notable clinical and genetic heterogeneity, but detailed data is lacking. Patients and Methods In this study, we retrospectively reviewed the clinical presentation, laboratory investigation, genetic and histopathological characteristics, and follow-ups of twenty-one pediatric mitochondrial myopathy cases from China. Results Twenty-four patients suspected with mitochondrial myopathy were enrolled initially and twenty-one were genetically identified. Fourteen patients were found to harbour mitochondrial DNA point mutations (14/21, 66.7%), including m.3243A>G (9/15, 60%), m.3303C>T (2/15, 13.3%), m.3302A>G (1/15, 6.7%), m.3250T>C (1/15, 6.7%), m.3251A>G (1/15, 6.7%), of whom twelve patients presented with progressive proximal mitochondrial myopathy (12/14, 85.7%). Three patients revealed large-scale deletion in blood or muscle tissue (3/21, 14.3%), presenting with Kearns-Sayer syndrome (1/3, 33.3%) or chronic progressive external ophthalmoplegia (2/3, 66.7%). Four patients were found to harbor pathogenic nuclear gene variants (4/21, 19.0%), including five variants in TK2 gene and two variants in SURF1 gene. During the follow-ups up to 7 years, ten patients developed cardiomyopathy (10/21, 47.6%), thirteen patients occurred at least once hypercapnic respiratory failure (13/21, 61.9%), six experienced recurrent respiratory failure and intubation (6/21, 28.6%), eight patients failed to survive (8/21, 38.1%). With nocturnal noninvasive ventilation of BiPAP, three patients recovered from respiratory failure, and led a relative stable and functional life (3/21, 14.3%). Conclusion Mitochondrial myopathy in children has great clinical, pathological and genetical heterogeneity. Progressive proximal myopathy is most prevalent. Mitochondrial DNA point mutations most common, while profound COX negative fibers in muscle biopsy usually suggest nuclear gene defects.